Efecto de la aplicación de efluente porcino sobre la incidencia de carbón del maní - Serri, Dannae Lilia; Bernanrdi Lima, Nelson; Campilongo Mancilla, Ernesto Javier; Perez Brandan, Carolina; Mathier, Diego Fernando; Bragachini, Marcos Ariel; Paredes, Juan Andrés; Monguillot, Joaquín Humberto; Rago, Alejandro Mario; Sosa, Nicolas; Vargas Gil, Silvina (Asociación Argentina de Fitopatólogos, 2022)
Poster